THE ROLE OF THE SYMPATHOADRENAL SYSTEM IN CARDIAC REMODELING AFTER MYOCARDIAL REVASCULARIZATION - Kholmirzayev S.A.; To‘xtamirzayev M.H. (International Journal of Literature and Language Studies, 2026)
This review article analyzes the role of the sympathoadrenal system in cardiac remodeling after myocardial revascularization in patients with ischemic heart disease. Restoration of coronary blood flow by percutaneous coronary intervention or coronary artery bypass grafting may improve myocardial perfusion, reduce ischemic burden and create conditions for reverse remodeling. However, post-revascularization recovery of left ventricular ejection fraction, ventricular geometry, myocardial fibrosis and hypertrophy depends not only on the anatomical success of revascularization, but also on neurohumoral regulation, autonomic balance, oxidative stress and structural myocardial changes. Persistent sympathoadrenal activation is associated with increased catecholamine secretion, elevated myocardial oxygen demand, calcium overload, β-adrenergic receptor desensitization, fibroblast activation, collagen deposition and pathological hypertrophy. Therefore, the integrated assessment of ejection fraction, left ventricular geometry, fibrosis, hypertrophy and sympathoadrenal activity may improve the understanding of residual cardiovascular risk after revascularization.